Pengaruh Penggunaan Gadget Terhadap Interaksi Sosial Anak Usia 5-6 Tahun di PAUD Mutiara Hati Kota Mataram - Maria Ulfa; Gunawan Gunawan; Baik Nilawati Astini; Ika Rachmayani (Indonesian Publication Center, 2023)
This research is motivated by the use of gadgets that continue to increase from year to year. The use of gadgets is not only used by adults but almost all circles including teenagers, children, and even toddlers have used gadgets in their daily lives. The tendency to excessive and inappropriate use of gadgets causes social interaction in children to be disrupted. This study aims to measure the effect of gadget use on social interaction of children aged 5-6 years in PAUD Mutiara Hati Mataram City. This research uses a type of quantitative research with ex-post facto methods. The sample used in this study was group B children in PAUD Mutiara Hati Mataram City, a total of 25 people. Sampling in this study uses saturated sampling, which is a sampling technique when all members of the population are used as samples using the Likert scale. Analytical techniques in the form of prerequisite tests, analysis and hypothesis tests. The analysis prerequisite tests include: normality test, homogeneity test, and linearity test. While the hypothesis test uses a linear regression test. The results of the hypothesis test show a p value (0.000) < 0.05 which means Ha is accepted and Ho is rejected, so it can be concluded that there is an influence between the use of gadgets on the social interaction of children aged 5-6 years in PAUD Mutiara Hati Mataram City. The influence between the use of gadgets and social interaction is positive, which means that the better or wiser the use of gadgets, the higher the child's social interaction and vice versa.